Solar slow magneto-acoustic-gravity waves: an erratum correction and a revisited scenario. Issue 4 (23rd April 2020) - Zurbriggen, E; Sieyra, M V; Costa, A; Esquivel, A; Stenborg, G
ABSTRACT: Slow waves are commonly observed on the entire solar atmosphere. Assuming a thin flux tube approximation, the cut-off periods of slow-mode magneto-acoustic-gravity waves that travel from the photosphere to the corona were obtained in Costa et al. In that paper, however, a typo in the specific heat coefficient at constant pressure c p value led to an inconsistency in the cut-off calculation, which is only significant at the transition region. Due to the abrupt temperature change in the region, a change of the mean atomic weight (by a factor of approximately 2) also occurs, but is often overlooked in analytical models for simplicity purposes. In this paper, we revisit the calculation of the cut-off periods of magneto-acoustic-gravity waves in Costa et al. by considering an atmosphere in hydrostatic equilibrium with a temperature profile, with the inclusion of the variation of the mean atomic weight and the correction of the inconsistency aforementioned. In addition, we measure the dominant periods near a particular active region (AR 1243) as observed by the Atmospheric Imaging Assembly (AIA) on-board the Solar Dynamic Observatory (SDO) on 2011 July 3 and compare them to our analytical results. The cut-off periods obtained analytically are consistent with the corresponding periods measured in observations.